A social exchange perspective on boosting customer loyalty through culturally competent servers. Issue 4 (19th May 2023) - Hsiao, Aaron; Ma, Emily (Jintao); Manfreda, Anita; Baker, Mandi; Xu, Jingjing
ABSTRACT: Limited research has examined how employees' cultural competency may influence customers experience and behaviors. Building on social exchange theory, this study proposed and tested a model focusing on how guest gratitude mediated the relationships between three dimensions of servers' cultural competency, cultural awareness, cultural knowledge, and cultural skills, on customers' future behavioral intentions. Using empirical data collected from cross-cultural service encounters in luxury hotels in Australia, findings of the study revealed that cultural awareness and skills were significantly related to guest gratitude that, in turn, significantly influenced customers future behavioral intention. This study contributes to social exchange theory by adopting gratitude as a mediator in the reciprocal relationship between servers' cultural competency and customer behavioral intentions. The study highlights the importance of training current hospitality employees and preparing future hospitality professionals. In particular, the findings emphasize the importance of enhancing hospitality employees' cultural competency in cross-cultural service encounters.